Relationship Between Pregnant Women's Knowledge About Labor Process With Anxiety Against Labor - Marwidah; Sari, Iramaya; Safruddin (Jurnal Life Birth, 2017)
According to WHO data estimates that there are 500,000 maternal deaths throughout the world every year, as many as 99 percents of deaths occur in developing countries. From this figure, it is estimated that almost one mother dies every minute due to pregnancy and childbirth. While in Indonesia the Maternal Mortality Rate (MMR) during childbirth is based on the 2015 Indonesian Health Demographic Survey where the MMR becomes 115 per 100,000 live births, so it still requires hard work from all components to reach the target. Research Objective To find out the Relationship between Knowledge of Pregnant Women About the Process of Labor and Anxiety Facing Labor in the Bonto Bangun Community Health Center, Rilau Ale District, Bulukumba Regency. Research design cross-sectional design. The population and sample in this study were pregnant women who were in the third trimester at the Bonto Public Health Center in the rilau ale sub-district of Bulukumba Regency as many as 34 people were taken using purposive sampling techniques using questionnaire measuring instruments. There is a Relationship between Knowledge of Pregnant Women About the Process of Childbirth With Anxiety Facing Childbirth at the Bonto Bangun Health Center, Rilau Ale District, Bulukumba Regency in 2015 with the results of a squared test obtained a value of 0,000 (> Î± = 0.5). Conclusions and Recommendations based on the results of research on the analysis of the relationship of knowledge of pregnant women about the process of childbirth with anxiety facing labor at the post-packaging bontobangun district rilau ale. In the interests of pregnant women in the face of childbirth required a high level of education, family support, age and parity in alleviating anxiety levels.